2018
DOI: 10.1159/000489777
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Techniques of Pancreatic Stump Management in Robot-Assisted Pancreaticoduodenectomy

Abstract: Background: Various technical improvements have decreased the morbidity and mortality after pancreaticoduodenectomy. However, postoperative pancreatic fistula (POPF) is the most feared complication, and the ideal technique for pancreatic reconstruction is undetermined. The aim of this study was to identify the risk factors and incidence of POPF with different types of pancreatic stump management after robot-assisted pancreaticoduodenectomy (RAPD). Materials and Methods: This study is a retrospective review of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Several techniques of pancreatic anastomosis have been proposed, including pancreato-gastrostomy (PG) and different techniques of PJ, including duct to mucosa and invagination [7][8][9][10][11][12]. Undoubtedly, one of the limitations of RAS for PD relates to the lack of a tactile feedback, since this may contribute to iatrogenic pancreatic parenchymal laceration during knots tying or from suboptimal suture line tension during continuous suturing [13].…”
mentioning
confidence: 99%
“…Several techniques of pancreatic anastomosis have been proposed, including pancreato-gastrostomy (PG) and different techniques of PJ, including duct to mucosa and invagination [7][8][9][10][11][12]. Undoubtedly, one of the limitations of RAS for PD relates to the lack of a tactile feedback, since this may contribute to iatrogenic pancreatic parenchymal laceration during knots tying or from suboptimal suture line tension during continuous suturing [13].…”
mentioning
confidence: 99%
“…In addition, in 11 studies chemical substances were injected into the main pancreatic duct to achieve a permanent occlusions. [8][9][10]22,26,27,29,31,33,34 No authors reported conflicts of interest regarding the substances used, neither sponsorship from manufacturing companies. In one study both chemical and mechanical occlusion were employed in two different groups of patients.…”
Section: Methods For Pancreatic Stump Occlusionmentioning
confidence: 99%
“…A total of 16 studies met the inclusion criteria and were selected for this meta-analysis [8][9][10][22][23][24][25][26][27][28][29][30][31][32][33][34] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations